Vascular plant specimens in Tribhuvan University Herbarium (TUH), Biratnagar, Nepal - Jha, Sasinath; Rai, Shiva Kumar; Koirala, Umesh; Niroula, Bhabindra; Bhagat, Indramani; Dhakal, Min Raj; Mandal, Tej Narayan (Nepalese Journal of Biosciences, 2013)
This report comprises the first list of 1019 specimens of vascular plants (Pteridophytes: 25 families and 106 species; Gymnosperms: 9 families and 19 species; Angiosperms: 136 families and 894 species) reposited in the “Tribhuvan University Herbarium (TUH)”, Department of Botany, Post Graduate Campus, Tribhuvan University, Biratnagar, Nepal. These specimens have been collected by students and teachers of the Department of Botany, Post Graduate Campus from various locations of eastern Nepal (tropical to temperate climates; 60 to 3000 m, msl altitudes) since the year 1992 onwards. For the purpose of easy access to the specimens, families within a taxon, genera within a family, and species within a genus are arranged alphabetically. Scientific names provided by Hara et al. (1978, 1979, 1982), Iwatsuki (1988), Koba et al. (1994), Siwakoti (1995), Press et al. (2000), Jha and Jha (2000), and Thapa (2002) have been adopted for the nomenclature of the reposited specimens. DOI: http://dx.doi.org/10.3126/njbs.v1i0.7475 Nepalese Journal of Biosciences 1: 83-95 (2011)